Antibiotic Prescription Patterns in Children with Pneumonia at the Waled Regional General Hospital in Cirebon Regency, West Java, 2023 - Istiharah, Sherin Nadia; Marfuati, Sri; Brajawikalpa, Rama Samara (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2026)
Irrational antibiotic use and inappropriate prescribing in pneumonia remain major public health concerns, as they contribute significantly to the development of antimicrobial resistance worldwide. This study aimed to describe the pattern of antibiotic prescribing for pneumonia patients under five years old treated at Waled Hospital, Cirebon Regency, in 2023. A descriptive study design was employed using medical record data, with total sampling applied to all eligible cases. Data were analyzed using univariate analysis and presented as frequencies and percentages. A total of 193 pediatric pneumonia cases were included, consisting of both inpatients and outpatients. Lobular pneumonia was the most common diagnosis in both groups. The majority of patients were one year of age. Third-generation cephalosporins were the most frequently prescribed antibiotic class for inpatients (62.3%) and outpatients (89.1%). Parenteral antibiotic formulations were predominantly administered to inpatients, whereas oral antibiotics were used for all outpatients. The duration of antibiotic therapy was appropriate in all cases. Adverse drug reactions were observed in a small proportion of inpatients and were not reported among outpatients. The predominant use of third-generation cephalosporins, particularly in outpatient settings, suggests a potential overreliance on broad-spectrum antibiotics and may reflect deviation from standard first-line treatment recommendations for pediatric pneumonia. These findings highlight the need for regular evaluation of prescribing practices and the implementation of antimicrobial stewardship programs to promote rational antibiotic use and reduce the risk of resistance.